The role of internal audit in reducing the risks of the electronic accounting information system - Mahmoud, Abdulmutallab Othman (Journal of Economic, Administrative and Legal Sciences, 2017)
This research aimed to clarify the effect of the utilization of electronic accounting information systems on the function of internal audit in government agencies. To put the research objective into effect, the research used the analytical descriptive approach and the field study approach. The research community, on the other hand, comprised of overall internal auditors of the government agencies in Sudan. In order to collect and analyze the field study data, the research used a questionnaire form, which distributed to a random sample, the amount of which is 100 internal auditors’ individuals of whom 99 individuals are the respondents, with a percentage amounts to 99%. The research used the Statistical Package for the Social Sciences program (SPSS) to perform the appropriate statistical treatments. The research has reached a number of research findings including the following: The level of internal auditors’ qualification at the public administration of internal audit of the government agencies, does not proportionate with the environment of electronically data processing. The more the internal auditor acquires knowledge and cognizance of the electronic data processing, the less risk of accounting procedures to take effect.